Fly girls : how five daring women defied all odds and made aviation history - O'Brien, Keith, 1973- (Houghton Mifflin Harcourt, 2018)
"High adventure and high ideals merge when a corps of intrepid female aviators battle to take part in the hugely popular air shows of the 1920s and 1930s. Ultimately, one of our heroines would win a race that earned her the right to be called America's best pilot"--